A companion to Ælfric - Magennis, Hugh; Swan, Mary (Brill's companions to the Christian tradition, 2009)
This collection provides a new, authoritative and challenging study of the life and works of A+lfric of Eynsham, the most important vernacular religious writer in the history of Anglo-Saxon England.